Wizard of the crow - Ngũgĩ wa Thiongʾo (New York Pantheon Books, 2006)
Set in the fictional Free Republic of Aburiria, Wizard of the Crow dramatizes with corrosive humor and keenness of observation a battle for the souls of the Aburirian people, between a megalomaniac dictator and an unemployed young man who embraces the mantle of a magician. Fashioning the stories of the powerful and the ordinary into a dazzling mosaic, in this magnificent work of magical realism, Ngugi wa'Thiong'o?one of the most widely read African writers?reveals humanity in all its endlessly surprising complexity.
Keywords: Power (Social sciences)--Fiction.